Udzielanie zamówień publicznych w ramach grupy kapitałowej a cena rynkowa w reżimie cen transferowych: [Conclusion of a public contracts within a capital group and the arm’s length price under the transfer pricing regime] (Studia Prawnicze / The Legal Studies, 2021)
Udzielenie zamówienia publicznego w ramach grupy kapitałowej wiąże się z problematyką weryfikacji rynkowości ustalonej w postępowaniu ceny w świetle regulacji z zakresu cen transferowych. Z dniem 1 stycznia 2019 r. do ustaw o podatkach dochodowych wprowadzono odesłania do Prawa zamówień publicznych, pozwalające na zastosowanie preferencji przy sporządzaniu dokumentacji cen transferowych przez niektóre podmioty działające w grupach kapitałowych funkcjonujących na rynku zamówień publicznych. W artykule przeanalizowano znaczenie badania rynkowości cen dla stosowania określonych instytucji prawa zamówień publicznych. Zidentyfikowano również sytuacje, w których możliwe jest udzielanie zamówień publicznych w ramach grup kapitałowych przy uwzględnieniu regulacji prawa zamówień publicznych dotyczących grup kapitałowych, statusu zamawiających i wykonawców, zamówień in-house i konfliktu interesów. Określono również skutki następczej zmiany w zakresie powiązań między zamawiającym a wykonawcą. Ustalenia te zestawiono z zakresem podmiotowym i przedmiotowym zasady ceny rynkowej wynikającej z regulacji cen transferowych. Zweryfikowano także prawidłowość i celowość wyłączeń obowiązku dokumentacyjnego u uczestników rynku zamówień publicznych i zaproponowaną korektę przepisów. The conclusion of a public contract within a capital group is related to the verification of compliance of the price established in the procedure with the arm’s length principle resulting from transfer pricing regulations. As of January 1, 2019, references to the Public Procurement Law were introduced to the Corporate Income Tax Act and Personal Income Tax Act, allowing for the application of preferences in the preparation of transfer pricing documentation by certain entities operating in capital groups operating within the public procurement market. The study analyzes the importance of establishing market prices for the application of specific institutions of public procurement law. Situations in which it is possible to award public contracts within capital groups have also been identified, taking into account public procurement law regulations relating to capital groups, the status of procuring entities and economic operators, in-house procurement and conflict of interest. The effects of the subsequent change in the relationship between the procuring entity and the economic operator have also been determined. These findings have been compared with the subjective and objective scope of the arm's length principle resulting from transfer pricing regulations. The correctness and purposefulness of the exemptions from the documentation obligation concerning the participants of the public procurement market have also been verified and correction of the transfer pricing regulations has been proposed.